Analysis of The Employability Skills Perception Gap: A Case Study of Teaching Factory Implementation at SMK Negeri 10 Makassar - Fitrah Asma Darmawan; Labusab; Aulia Sabril (Jurnal MEKOM (Media Komunikasi Pendidikan Kejuruan), 2026)
Purpose – Vocational education continues to face a persistent competency gap between graduates and industry demands. The Teaching Factory (TeFa) model at SMK Negeri 10 Makassar has been implemented as a strategic approach to enhance students’ employability skills. This study aims to evaluate the implementation of the TeFa model and assess its effectiveness in developing students’ work character and technical competencies. Methods – A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 54 students through structured questionnaires, while qualitative data were obtained through observations and in-depth interviews with 12 teachers and industry partners. Findings – The results show moderate implementation quality, with SOP compliance at 70.3% and effective communication at 68.5%. A notable perception gap was identified, in which students rated their discipline (61.1%) and time management (64.8%) highly, whereas teachers and industry partners perceived these areas as major weaknesses. Furthermore, 38.9% of students reported a neutral perception of the improvement in their hard skills, indicating infrastructure constraints and the phenomenon of pseudo-discipline. Although the TeFa model demonstrates potential in character building, its effectiveness in strengthening technical competencies remains limited. Research implications – Findings from this single-case study are contextual to SMK Negeri 10 Makassar and should be further validated in broader vocational education contexts. This study recommends the adoption of “Industrial Mirroring” strategies and systematic role rotation to better align student perceptions with industrial standards. Originality – This study contributes by revealing the perception gap between students, teachers, and industry partners regarding work character and technical competency development within the Teaching Factory implementation in vocational education.